Perempuan dalam Kesunyian: Mengenal Kehidupan dan Karya-karya Siti Rukiah Kertapati (1927-1996) - Peggy Nirwanjanti; Ratu Husmiati; Kurniawati Kurniawati (Historia Madania: Jurnal Ilmu Sejarah, 2023)
This article aims to introduce the figure of Siti Rukiah Kertapati as one of Indonesia's female writers. Through her works, we can see the turbulent revolution around the 1940s to 1960s from the perspective of the common person, especially that of a woman. The narrative of women in the revolution presented by Siti Rukiah Kertapati is not grandiose by making the main character a "hero" in the story. The figure of a young woman who is restless between her heart and mind makes anyone who reads it also relate. With most of the themes carrying love stories and human inner struggles, Siti Rukiah Kertapati can bring a simple narrative but is still able to make it an interesting read. The method used is historical with a descriptive-narrative approach. The research data is taken from short stories collected in the book Tandus and the novel Kejatuhan dan Hati with interpretations made by the writer. The results of this research are expected to be useful for the general public to recognize and appreciate the works of Siti Rukiah Kertapati.Keywords: Siti Rukiah Kertapati, women, literature